Caracterização físico-química do biodiesel de algodão - Carvalho, Adeilson (2018)
There are a number of environmental and energy motivations regarding the increasing use of renewable fuels. Biodiesel is one of the renewable alternatives to the use of fossil diesel and its use has grown worldwide. In Brazil, there is a very favorable condition for the cultivation of oilseeds, and biodiesel appears as a proposal for environmental, energy and social solution. The use of biodiesel in Brazil has been growing since 2004. This study aimed at characterizing the physicochemical properties of biodiesel produced from cotton oil and its mixture with commercial diesel in different doses, for the purpose of replacing mineral fuel. Commercial Diesel (DC) was mixed with biodiesel of cotton oil (B100) in different proportions, as described: 98% DC and 2% B100; 94% DC and 6% B100; 88% DC and 12% B100; 80% DC and 20% B100; 76% DC and 24% B100; 50% DC and 50% B100; 20% DC and 80% B100. The experiment design was completely randomized, with 3 replications. The following analyses were carried out: visual aspect, color, acidity index, viscosity, density and flash point. It was found that the rheological behavior of diesel, B100 and all BX mixes is Newtonian. The mixtures B50 and B80 showed viscosity, density and acidity index above the maximum limit recommended by the ANP 30/2016 resolution. Biodiesel B100 presented acidity index above of that established by the current legislation (ANP 45/2014 resolution). The production of biodiesel from cotton oil is a viable alternative, since when used in mixtures with mineral diesel up to the limit of 24%, it meets the specifications of the ANP 30/2016 resolution.